Software Geogebra no ensino de funcões: revisão da literatura a partir das produções discentes nas dissertações do PROFMAT - PEREIRA, Alvimar de Jesus Schalcher (2018)
This study aims at reviewing the literature of the graduated students from the Post-graduation Program of Mathematics in National Network ? PROFMAT from 2016 to 2018, in order to relate the GEOGEBRA software to the study of Elementary Functions. The selected contend for this analysis is composed by eighteen dissertations published on PROFMAT website, firstly the titled as GeoGebra, than the ones filtered by the related to the functions themed. In this is presented a comparison of the selected material in which their objectives, results, theorical references, research questions, research subjects, methodology used are shown. Therefore, this survey presents indicates that may support future investigations, highlighting the lack in some points that still need to be searched within the discussed theme. As well, recommendations to the use and improvement of GeoGebra to teacher and their pedagogical work in the classroom, in special the elementary functions teaching. It is hoped this study will lead the reader to possible discussions to the teacher?s role in mathematics teaching, as well, the needing of adding new technologies, aware of updatings in the teaching methods to come in the future based on the changings that there have been in our society.